Cytotoxicity and Antiviral Activities of Haplophyllum tuberculatum Essential Oils, Pure Compounds, and Their Combinations against Coxsackievirus B3 and B4 - Hamdi, Assia; Halouani, Aymen; Aouf, Ines; Viaene, Johan; Marzouk, Belsem; Kraiem, Jamil; Jaïdane, Hela; Heyden, Yvan Vander (Planta Medica, 2021)
Haplophyllum tuberculatum is a plant commonly used in folk medicine to treat several diseases including vomiting, nausea, infections, rheumatism, and gastric pains. In the current study, H. tuberculatum essential oils, hydrosols, the pure compounds R-(+)-limonene, S-(−)-limonene, and 1-octanol, as well as their combinations R-(+)-limonene/1-octanol and S-(−)-limonene/1-octanol, were screened for their cytotoxicity on HEp-2 cells after 24, 48, and 72 h, and then tested for their activity against Coxsackievirus B3 and B4 (CV-B3 and CV-B4) at 3 different moments: addition of the plant compounds before, after, or together with virus inoculation. Results showed that the samples were more cytotoxic after 72 h than after 24 h or 48 h cell contact. However, the combinations R-(+)-limonene/1-octanol and S-(−)-limonene/1-octanol showed less effect on HEp-2 cells than pure R-(+)-limonene and S-(−)-limonene after 24 h, 48 h, and 72 h. 1-octanol exhibited the highest concentration causing 50% cytotoxicity (CC50) on HEp-2 cells after 24 h (CC50 = 93 µg/mL) and 48 h (CC50 = 83 µg/mL). The antiviral assays showed that the tested samples exhibited potent inhibition of CV-B. IC50 values ranged from 0.66 µg/mL to 28.4 µg/mL. In addition, CV-B3 was more sensitive than CV-B4. Both CV-B strains are more inhibited when cells were pretreated with the plant compounds. The hydrosols have no effect, neither on HEp-2 cells nor on the virus. 1-octanol, S-(−), and R-(+)-limonene/1-octanol had important selectivity indexes over time. Although essential oils had potent antiviral activity, they can be considered for application in the pretreatment of cells. However, 1-octanol and the combinations are within the safety limits, and thus, they can be used as an active natural antiviral agent for CV-B3 and CV-B4 inhibition.
Keywords: Haplophyllum tuberculatum; Rutaceae; essential oils; pure compounds; Coxsackievirus B; cytotoxicity; selectivity index